2020
DOI: 10.1186/s13054-020-03098-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and predictors of 60-day mortality in 239 critically ill patients with COVID-19: a multicenter retrospective study from Wuhan, China

Abstract: Background The global numbers of confirmed cases and deceased critically ill patients with COVID-19 are increasing. However, the clinical course, and the 60-day mortality and its predictors in critically ill patients have not been fully elucidated. The aim of this study is to identify the clinical course, and 60-day mortality and its predictors in critically ill patients with COVID-19. Methods Critically ill adult patients admitted to intensive care units (ICUs) from 3 hospitals in Wuhan, China, were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
211
4
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(263 citation statements)
references
References 46 publications
24
211
4
13
Order By: Relevance
“…We failed to show any differences in mortality between mechanically ventilated versus non-mechanically ventilated patients [ 3 , 4 , 7 , 8 ] but our retrospective study was significantly underpowered. However, subgroup analysis revealed higher body mass index and rate of nosocomial acquired infections in the COVID-19 mechanically ventilated subgroup of patients versus the non-mechanically ventilated group, which is in accordance with previous reports [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ]. In our study, the incidence of nosocomial acquired infections based on strict clinical criteria was 19.6%, which although an important cofactor did not affect mortality during TCZ therapy.…”
Section: Discussionsupporting
confidence: 92%
“…We failed to show any differences in mortality between mechanically ventilated versus non-mechanically ventilated patients [ 3 , 4 , 7 , 8 ] but our retrospective study was significantly underpowered. However, subgroup analysis revealed higher body mass index and rate of nosocomial acquired infections in the COVID-19 mechanically ventilated subgroup of patients versus the non-mechanically ventilated group, which is in accordance with previous reports [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ]. In our study, the incidence of nosocomial acquired infections based on strict clinical criteria was 19.6%, which although an important cofactor did not affect mortality during TCZ therapy.…”
Section: Discussionsupporting
confidence: 92%
“…The search strategy identified 7,385 records: 6,528 from PubMed, 465 from CNKI, 322 from Wangfan, and 70 from other sources (Figure 1). After excluding duplicated and irrelevant records, 16 studies were included in this meta-analysis with a total of 10,624 COVID-19 cases ( Table 1) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Thirteen studies derived from China, while one study came from the USA, one from Spain and one from India.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…This combination is one of the most commonly found in adults around the world 27 and can be attributed to the fact that multiple organ failure is associated with increased levels of plasminogen, which produces coronary thrombosis and pulmonary embolism. 30 In general, we found that a greater presence of NCDs increases CFR because it re ects multiorgan dysfunction, severity, and worse prognosis. [31][32] We observed a triple interaction between number of NCDs, age, and sex.…”
Section: Discussionmentioning
confidence: 65%